ANALISIS EFEKTIVITAS PAJAK DAERAH, RETRIBUSI DAERAH, HASIL KEKAYAAN DAERAH YANG DIPISAHKAN DAN LAIN-LAIN PENDAPATAN ASLI DAERAH YANG SAH SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI ACEH - Raudhatinur Raudhatinur; Endang Surasetyo Ningsih (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this research isto analyze the effectiveness of local taxes, local retribution, Local own source assets and others Legitimate local revenue and its contribution to the local revenue of districts/ cities in Aceh Province. The method in this research is using descriptive quantitative methods, with effectiveness analisys and contribution analisys as the instrument of the analisys.The result of this research shows that the average of the effectiveness in period (2013-2017) of the Local Tax is89,91 % (quite effective), local retribution is 77,87 % (less effective),Local own source assetsis 107,06 % (very effective) , and others Legitimate local revenueis 102,06% (very effective. The average of the contribution in period (2013-2017) of local taxes is 15,15 % (less), local retribution is 20,46 % (medium), Local own source assets is 4,89 % (very less), and others Legitimate local revenue is 50,46 % (very good)